Heterologous antigen extract in ELISA for the detection of human IgE anti-Strongyloides stercoralis - Costa-Cruz, Julia Maria; Madalena, Joaquina; Silva, Deise Aparecida de Oliveira; Sopelete, Mônica Camargo; Campos, Dulcinéa Maria Barbosa; Taketomi, Ernesto Akio (Revista do Instituto de Medicina Tropical de São Paulo, 2003)
Strongyloides ratti larval extract was used for the standardization of ELISA to detect genus-specific IgE in human strongyloidiasis. Forty serum samples from monoinfected patients shedding S. stercoralis larvae (Group I), 40 from patients with other intestinal parasites (Group II), and 40 from copronegative healthy subjects (Group III) were analyzed. Genus-specific IgE levels (ELISA Index: EI) were significantly higher in the group I (EI = 1.43) than groups II (EI = 0.70) and III (EI = 0.71), showing positivity rates of 55%, 2.5% and 0%, respectively. Similarly, sera from copropositive patients had significantly higher levels of total IgE (866 IU/mL) as compared to those from group II (302 IU/mL) and III (143 IU/mL). A significant positive correlation was found between levels of Strongyloides specific-IgE and total IgE in sera from patients with strongyloidiasis. In conclusion, S. ratti heterologous extract showed to be a useful tool for detecting genus-specific IgE by ELISA, contributing for a better characterization of the immune response profile in human strongyloidiasis.